Urea A Significant Clinical Marker of Vaso-Occlusive Crises in Sickle Cell Disease (Medical Forum Monthly, 2022)
Objective: To measure serum urea level of Sickle Cell Disease (SCD) patients in pain free steady state and compare it with the levels taken at start, during and on recovery of Vaso-occlusive crises (VOC).Study Design: Prospective observational studyPlace and Duration of Study: This study was conducted at the Lifecare Molecular & PCR Lab Services from May 2018 till May 2020 for a period of more than two years.Materials and Methods: 25 diagnosed cases of SCD aged 12 to 22 years were included. It was a multidisciplinary approach study including the anesthetist for pain management when required. UCE (Urea, creatinine and electrolytes) was taken in the steady pain free state, at the start, during and on resolution of VOC. The steady state urea level was compared with the other samples taken during VOC using a student’s unpaired two-tailed ’t’ test, a p value <0.005 was taken as significant.Results: 36 episodes of VOC were analyzed. Mean serum urea level in steady state was 2.8 +- 0.8 mmol/L which dropped to 1.9 +- 1.1 at the time of presentation, reached to 1.5 +- 0.9 (p< 0.0005) during VOC with gradual return to steady state level as the crises settled.Conclusion: A significant drop in urea levels during VOC with a return to steady state level was seen defining VOC and its resolution.